Thermal stabilities of poly(N-acryloyl-N?-methylpiperazine), its blends with poly(methyl methacrylate), and poly(N-acryloyl-N?-methylpiperazine-co-methyl methacrylate) - Coskun, M; Barim, G; Demirelli, K (Taylor & Francis Inc, 2006)
Poly(N-acryloyl-N'-methylpiperazine-co-methyl methacrylate)s, poly(methyl methacrylate), poly(N-acryloyl-N'-methylpiperazine), have been prepared by free radical polymerization using AIBN as initiator. Blends of the homopolymers in similar composition with those of the copolymers have been prepared by casting films from CHCl3 solution, followed by drying for a few days. The homopolymer, the copolymers and the blends have been characterized by differential scanning calorimetry (DSC), FTIR spectroscopy and H-1 NMR spectroscopy. The single glass transitions observed from DSC curves of the blends indicated that the blend components were miscible. Thermal stabilities of the blends and the copolymers have been investigated by thermogravimetric analysis (TGA) and FTIR as comparing with each other and those of the homopolymers. In thermal degradation of poly(N-acryloyl-N'-methylpiperazine), during product identification by gas chromatography-mass spectrometry (GC-MS), N-methyl piperazine has been detected as a main product in the ratio of 70.8% as GC peak area. Some differences in thermal behavior of the copolymer and the blend in similar composition have been observed.
Keywords: thermal stability; poly(N-acryloyl-N '-methylpiperazine); blend; poly(methyl methacrylate)